The I ching : points of balance and cycles of change - Jones, Peggy (Karnac Books, 2008)
"Among the many available versions of the I Ching, this new rendering by Jungian analyst Peggy Jones deserves a special place. It presents the wisdom of the ancient Chinese oracle in lucid, psychological language that speaks directly and insightfully to contemporary situations. Remaining faithful to the spirit of the original, Peggy Jones's I Ching guides us sagely in the task of maintaining psychological balance in a world of rapid change"--Page 4 of cover